Pan-cancer analysis identifies LIFR as a prognostic and immunological biomarker for uterine corpus endometrial carcinoma - Zhang, Fang; Wang, Yali; Li, Hongjuan; Li, Li; Yang, Xiaofeng; You, Xiaoyan; Tang, Lina (Frontiers in Oncology, 2023)
Background Leukemia inhibitory factor (LIF) exhibits significant tumor-promoting function, while its cognate receptor (LIFR) is considered to act as either a tumor promoter or suppressor. Dysregulation of LIF and LIFR is associated with the initiation, progression and metastasis of multiple cancer entities. Although increasing numbers of studies are revealing an indispensable critical role of LIFR in tumorigenesis for various different cancers, no systematic analysis of LIFR has appeared thus far. Methods Here, we comprehensively analyzed the expression profile and prognostic value of LIFR, and correlations between LIFR and the infiltration of immune cells and clinicopathological parameters across different tumor types using several bioinformatic tools. The expression profile of LIFR in various tumor types and clinical stages was investigated using the TIMER2 and GEPIA2 databases. Genetic alternations of LIFR were extracted from cBioPortal. The prognostic value of LIFR was assessed using GEPIA2 and Sanger box databases, and correlations between LIFR expression and immune infiltration were analyzed using the CIBERSORT method and TIMER2 database. The correlations between LIFR expression and immune and stromal scores were assessed using ESTIMATE. We also analyzed correlations between LIFR and immunoregulators. Finally, we detected an effect of LIFR on Uterine Corpus Endometrial Carcinoma (UCEC) and evaluated the expression level of LIFR in clinical UCEC samples. Results Aberrant expression of LIFR in cancers and its prognosis ability, especially in UCEC was documented. Significantly lower levels of LIFR expression level correlated with better prognosis in multiple tumor types. LIFR expression was positively correlated with the abundance of cancer-associated fibroblasts (CAFs) and endothelial cells in the tumor microenvironment. Additionally, LIFR expression was strongly associated with the presence of immune modulators and checkpoint genes. Overexpression of LIFR suppressed the migration and invasion of UCEC cells in vitro. Conclusion Our pan-cancer detection data provided a novel understanding of the roles of LIFR in oncogenesis.